Synthesis of Difluoromethyl Chromono[3,2-c]pyrazolines/pyrazoles by [3+2] Cycloaddition Reaction of Difluoroacetohydrazonoyl Bromides with 3-EWG-Chromones - Wang, Ke-Hu; Liang, Xiuwen; Luo, Wenjing; Chen, Maizhuo; Wang, Junjiao; Huang, Danfeng; Hu, Yulai (Synthesis, 2024)
A highly convenient and straightforward strategy for the synthesis of difluoromethyl substituted tricyclic fused chromono[3,2-c]pyrazolines/pyrazoles is developed via [3+2]-cycloaddition of difluoroacetohydrazonoyl bromides to chromene derivatives bearing an electron-withdrawing group at the 3-position. The reaction has the advantages of mild conditions, good tolerance of functional groups, and simple operation.
Keywords: cycloaddition reaction; chromono[3,2-c]pyrazolines; chromono[3,2-c]pyrazoles; difluoroacetohydrazonoyl bromides; 3-EWG chromones